Enhancing Students’ Narrative Writing Skills Through Mind Mapping Technique at Grade XI-3 SMA - Marino Sihombing; Dumaris E. Silalahi (STKIP Taman Siswa Bima, 2025)
Writing skill is a crucial component of English language learning; however, it remains one of the most challenging skills for many senior high school students, particularly in narrative writing. In the current classroom context, students of grade XI-3 SMA experience specific difficulties in generating ideas, developing coherent story plots, and organizing events logically. Many students struggle to construct complete narrative structures, including clear orientation, complication, and resolution, which often results in fragmented and incoherent texts. Common problems include poor event sequencing, limited vocabulary, weak paragraphs, and low cohesion. These difficulties are closely related to instructional practices that emphasize the final written product rather than the writing process. Students are frequently asked to write narrative texts without sufficient guidance on planning, organizing, and developing ideas systematically. Consequently, students feel confused, unmotivated, and anxious, which negatively affects their writing performance. This situation indicates the urgent need for an effective instructional technique. Mind Mapping was selected to address these issues because it helps students brainstorm ideas, organize story elements, and maintain narrative coherence. This Classroom Action Research involving 34 students showed improved writing achievement, with mean scores increasing from 65.21 to 82.46 and more students reaching Good and Very Good categories overall.